Next-generation sequencing analysis of multiplex families with atypical psychosis. Issue 1 (December 2018) - Okayama, Tatsushi; Hashiguchi, Yasuyuki; Kikuyama, Hiroki; Yoneda, Hiroshi; Kanazawa, Tetsufumi
Abstract Atypical psychosis (similar to acute and transient psychotic disorder, brief psychotic disorder) is highly heritable, but the causal genes remain unidentified. We conducted whole-genome sequencing on multiplex Japanese families with atypical psychosis. The patient group of interest shows acute psychotic features including hallucinations, delusions, and catatonic symptoms while they often show good prognosis after the onset. In addition to the next-generation analysis, HLA typing has been conveyed to check the similarity with autoimmune disease, such as systemic lupus erythematosus (SLE). Shared causal polymorphisms in the Deleted in Colorectal Carcinoma, Netrin 1 receptor (DCC) gene were found in one multiplex family with three patients, and variants in the RNA 3′-Terminal Phosphate Cyclase (RTCA) and One Cut Homeobox 2 (ONECUT2) genes were found to be shared in seven patients. Next-generation sequencing analysis of the MHC region (previously suggested to be a hot region in atypical psychosis) using HLA typing (HLA-DRB1) revealed a common vulnerability with SLE (systemic lupus erythematosus) among five patients. This finding demonstrates the shared etiology between psychotic symptoms and autoimmune diseases at the genetic level. Focusing on a specific clinical phenotype is key for elucidating the genetic factors that underlie the complex traits of psychosis.